Comparison of the effect of a morton’s extension on plantar pressure distribution in female and male patients without deformities: A pre-post test study - Anna Sánchez-Serena; Ricardo Becerro-de -Bengoa-Vallejo; Marta Elena Losa-Iglesias; Eduardo Pérez-Boal; Jorge Posada-Ordax; Eva María Martínez-Jiménez; Bibiana Trevissón-Redondo; Vicenta Martínez-Córcoles; Daniel López-López; Israel Casado-Hernández (PLoS ONE, 2025)
Background Plantar pressure measurement has become increasingly relevant in fields such as sports performance, rehabilitation, and podiatry. Its outcomes are influenced by factors including foot morphology, body weight, joint mobility, and biological sex, with documented anatomical and physiological differences between men and women potentially affecting load distribution. Morton’s extension, an orthotic device used to restore first ray function, has shown clinical efficacy in managing forefoot pathologies. However, limited research has examined its biomechanical effects with respect to sex. This study aimed to evaluate the differential impact of Morton’s extension on plantar pressure distribution in men and women, under both static and dynamic conditions. Methods A sex comparing clinical trial intervention study was conducted with 18 men´s feet (38.11 ± 15.49 years) and 32 women´s feet (41.63 ± 15.22 years), who underwent plantar pressure assessments using a calibrated platform before and after the application of a Morton extension. Static and dynamic measurements were recorded under both conditions to evaluate changes in pressure distribution. A mixed models static analysis was done to check that there are differences by sex on foot. Findings The following results summarize statistically significant differences observed between sexes under both static and dynamic conditions, with and without Morton’s extension. In static pressures without Morton’s extension, statistically significant results were found in P.Max.Rtp.(kPa) (p = 0.006) and Medium.pressure.Rtp.(kPa) (p < 0.001). With Morton’s extension in static conditions, significant differences were observed in P.Max.1M.(kPa) (p = 0.034), P.Max.Rtp.(kPa) (p = 0.017), and Medium.pressure.Rtp.(kPa) (p = 0.003). In dynamic pressures, before the intervention, statistically significant differences between sexes were observed in P.Max.1M.(kPa) (p = 0.023), Medium.pressure.1M.(kPa) (p = 0.008), Contact.Surfaces.(cm²) (p = 0.008), and Step.duration.(Milliseconds) (p = 0.048). After the intervention, additional significant differences were found in Contact.Surfaces.(cm²) (p = 0.009). Conclusion The combined evidence indicates that Morton’s extension elicits clinically meaningful, sex-dependent alterations in plantar loading. By applying mixed-effects models we uncovered subtle intra- and interindividual patterns that conventional analyses may overlook. These results support sex-specific orthotic dosing (height/geometry) and argue for individualized prescription to maximize load redistribution, reduce focal overpressure and prevent site-specific pathology. Future work should validate optimal orthotic designs using dynamic 3D gait analysis and computational modelling.